Direptio Syrakuz – kilka uwag na temat grabieży dzieł sztuki w okresie rzymskiej Republiki - Jarych, Adam Jakub (Acta Universitatis Lodziensis. Folia Archaeologica, 2017)
Direptio Syracuse (212 BC) from the statues and paintings, it was not the first such case in the world of republican Rome. However, for the first time a Roman general, in this case Mark Claudius Marcellus, exposed the spoils in such an expressive way, during ovatio in Rome. Thereby, he launched the „Hellenization of art” of ancient Rome. This article draws the attention to a number of factors relating to the looting of Greek art, which was becoming more and more popular during the first Punic War. Moreover, it focuses on the aesthetic changes in the Roman art in the third and second century BC.